Changes in Consumer Behavior in Water Use Resulting in an Increase in Monthly Water Account Arrears Since the Covid-19 Pandemic (Case Study of PDAM Tirtanadi Cemara Branch, North Sumatra Province) - Muslimatul Husnah Batubara; Wahyu Syarvina (Penerbit Jurnal Indonesia, 2022)
Changes in Consumer Behavior in Water Use Result in an Increase in Monthly Water Account Arrears Since the Covid-19 Pandemic, at PDAM Tirtanadi, Cemara Branch, North Sumatera Province. This research is a quantitative descriptive that aims to determine the level of service in the company's management of customers in paying for clean water use, and aims to see the causes and obstacles that occur to the increase in arrears in water accounts which have increased due to changes in water use since the covid-19 pandemic. The unit of observation in this study is the report on water account arrears for the months November 2020 – November 2022. The types of data used in this study are primary data and secondary data. The method of analysis in this study is from supporting document sources, and uses descriptive statistics on the report of the arrears balance, providing an overview or description by displaying a diagram of the monthly increase in water account arrears since the covid-19 pandemic. The results of this study indicate that the service and management of the company are good and well maintained, but there has been a change in consumer behavior in usage since the covid-19 pandemic which has increased which has resulted in an increase in monthly water payment account arrears.